2019
DOI: 10.21815/jde.019.070
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Medication Documentation in Electronic Health Records: Dental Students' Self‐Reported Behaviors and Charting Practices

Abstract: The aim of this two‐part study was to assess third‐ and fourth‐year dental students' perceptions, self‐reported behaviors, and actual charting practices regarding medication documentation in axiUm, the electronic health record (EHR) system. In part one of the study, in fall 2015, all 125 third‐ and 85 fourth‐year dental students at one U.S. dental school were invited to complete a ten‐item anonymous survey on medication history‐taking. In part two of the study, the EHRs of 519 recent dental school patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Additionally, despite using a small sample size, an in-depth exploratory analysis was conducted on each medical consult utilizing a minimum of 17 components. Nevertheless, the results regarding the reasons for seeking medical consults are consistent with other studies and related reports ( 15 – 17 , 21 ). Like other studies conducted in a single setting, the findings from this study have limited generalizability outside of the IUSD or the academic dental environment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, despite using a small sample size, an in-depth exploratory analysis was conducted on each medical consult utilizing a minimum of 17 components. Nevertheless, the results regarding the reasons for seeking medical consults are consistent with other studies and related reports ( 15 – 17 , 21 ). Like other studies conducted in a single setting, the findings from this study have limited generalizability outside of the IUSD or the academic dental environment.…”
Section: Discussionsupporting
confidence: 92%
“…The patient's inability to provide enough medical information to continue with care could have prompted dental providers to seek medical consults. A recent survey of dental providers ( 21 ) in our institution reported patients' limited knowledge of their medications, as a significant barrier to obtaining complete medication history. Other studies also suggest that patients, especially older patients with multiple chronic conditions, have difficulty recalling their medical and medication histories ( 22 , 23 ), thus negatively affecting dental providers' patient care.…”
Section: Discussionmentioning
confidence: 99%
“…16 A few studies have evaluated the completeness and correctness of EDR data in academic institutions to identify gaps and improve dental students' training for patient care documentation. [20][21][22] These studies indicate the need to establish a systematic process to evaluate the data quality of EDR-derived datasets and to promote fidelity and reproducibility of secondary data analysis.…”
Section: Background and Significancementioning
confidence: 99%
“…Furthermore, patient-reported medical histories place a significant burden on patients who may have limited medical knowledge, especially older patients with multiple chronic conditions. Studies have reported patient's difficulty recalling their medical and medication histories, which may negatively affect the dental care process ( 8 10 ). Therefore, to obtain complete information, the DCs will consult the patients' physicians through medical consults.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to establish uninterrupted interaction between dental and medical settings to overcome inconsistent documentation and communication problems, and to improve access to up-to-date patient medical history. This interaction could help avoid the potential for fatal accidents and maintain patient safety during dental care ( 1 , 5 , 6 , 8 , 12 ).…”
Section: Introductionmentioning
confidence: 99%